Role of Surgeon in the Causation of Surgical Wound Infection in Non-traumatic Emergency Laparotomy - Mohammad, Din; Begum, Mahbuba; Talukder, Abdur Rabban; Salam, Md. Abdus (Journal of Science Foundation, 2017)
Background: Surgeon has a vital role during operation related with wound infection. Objective: The purpose of the present study was to see the role of wound infection of non-traumatic emergency laparotomy surgeries. Methodology: This descriptive cohort study was carried out in the Department of Surgery at Dhaka Medical College, Dhaka from July 1997 to June 1998 for a period of 1(one) year. Pre-operative patients were carefully assessed for any host factors related to wound infection. Different per-operative factors that influence the rate of postoperative wound infection were also analyzed. Swabs were taken from the suspected postoperative wound and sent for bacteriological examination. The details related to the surgeon were recorded according to their experience. Result: In this series, 100 cases of emergency laparotomies (non-traumatic) were analyzed. Wound infection rate of specific type of operation were 12.5%, 20.0%, 6.6%, 40.0%, 40.0%, 33.3%, 50.0%, 50.0%, and 100.0% in duodenal ulcer perforation, pre-pyloric and gastric ulcer perforation, acute appendicitis, burst appendix, ileal perforation, small intestinal obstruction due to bands and adhesions, volvulus of sigmoid colon, obstructed inguinal hernia, generalized peritonitis due to puerperal sepsis respectively. Surgical site infections are more commonly occur in the operation performed by inexperience younger surgeon (44.4%). Conclusion: The rate of wound infection of non-traumatic emergency laparotomy cases are frequently found in the operation performed by inexperience younger surgeon. Journal of Science Foundation 2016;14(2):52-55